Inorganic-organic melted-extruded hybrid filaments and medical applications thereof - CARPENTER KIMBERLY A; SHALABY SHALABY W; CLINKSCALES KENNETH W (2008)
This invention deals with a family of inorganic-organic hybrid, melt-extruded filaments having variable cross-sectional geometry with a cross-sectional area ranging between 100 mu2 and 4 mm2, wherein the inorganic component comprises at least 10 weight percent of the total system and is present as dispersed micro-/nanoparticles in an organic absorbable or non-absorbable matrix representing no more than 90 weight percent. Hybrid filaments are particularly useful for the production of absorbable/disintegratable coil components of an absorbable/disintegratable endoureteral stent and radiopaque surgical markers or sutures.